1998
DOI: 10.1089/clm.1998.16.117
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study about the Removal of Smear Layer by Three Types of Laser Devices

Abstract: Objective: The aim of this study was to analyze the effectiveness of three types of laser, argon, Nd:YAG, and Er:YAG, to remove the smear layer from the prepared root canal walls in vitro. Methods: After cleaning and shaping by step-back preparation, 32 human extracted maxillary molar teeth were divided randomly into four groups. Root canals in group 1 (Gl) were unlased and were irrigated by 17% EDTA. In group (G2), root canals were irradiated by argon laser at the parameters of 1 W, 50 mj, and 5 Hz. In group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
19

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(83 citation statements)
references
References 23 publications
(16 reference statements)
2
62
0
19
Order By: Relevance
“…[46][47][48] Power is one of those parameters. According to the study by Takeda et al the power of 1/2 W is adequate for clearing the smear layer, 11,49,50 moreover, the power of 1/2 W is adequate for disinfecting the canal. 51 Accordingly, in the present study, because the primary teeth are chosen and there is structural difference between primary and permanent teeth, the least power (1 W) used in other studies is chosen and examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[46][47][48] Power is one of those parameters. According to the study by Takeda et al the power of 1/2 W is adequate for clearing the smear layer, 11,49,50 moreover, the power of 1/2 W is adequate for disinfecting the canal. 51 Accordingly, in the present study, because the primary teeth are chosen and there is structural difference between primary and permanent teeth, the least power (1 W) used in other studies is chosen and examined.…”
Section: Discussionmentioning
confidence: 99%
“…48 Water or air sprays are some of the efficient factors in preventing thermal damage. [49][50][51] The study by Theodoro et al showed that applying laser for 30 seconds with water spray can decrease temperature (-2.2 ± 2.5°C). 52 It should be taken into consideration that using too much water or air cooling results in energy absorption and decreased ablation effect of laser.…”
Section: Anti-bacterial Effect Of Er:yag Laser On Enterococcus Faecalismentioning
confidence: 99%
“…Takeda et al (52) showed that irrigation with 17% EDTA, 6% phosphoric acid and 6% citric acid was not able to remove the entire smear from the root-canal system. Acidic solutions cause erosion and widening of tubules.…”
Section: Laser Applications In the Removal Of The Root Canal Filling mentioning
confidence: 99%
“…6 The erbium, chromium: Yttrium-scandium-gallium-garnet (Er,Cr:YSGG) laser is approved by the Food and Drug Administration for cleaning, shaping, and enlarging the root canal. 7 Previous studies have tested the ability and effects of this laser on root canal walls and have indicated that the Er,Cr:YSGG laser is a suitable instrument for the removal of smear layer in root canals. Furthermore, George et al 8 investigated the ability of Er,Cr:YSGG lasers equipped with conical firing tips to remove smear layer from apical third of the root canal and showed a laser activation of EDTA and better performance of conical fiber tips for improving the action of EDTA in removing smear layer.…”
Section: Introductionmentioning
confidence: 99%